Stored red blood cell transfusions: Iron, inflammation, immunity, and infection - Hod, E.A. (Transfus Clin Biol, 2012)
The potential adverse effects of transfusion of red blood cells after prolonged storage have been hotly debated. During refrigerated storage, red blood cells are damaged, a process known as the red blood cell “storage lesion.” We hypothesized that the delivery of a bolus of iron derived from these rapidly cleared, damaged, red blood cells is responsible for some of the adverse effects of transfusion. Iron may play a role in producing a pro-inflammatory response to transfused red blood cells, potentially through the effects of reactive oxygen species on stress pathways and inflammasome activation. Furthermore, the excess iron may impair the host’s ability to combat infection by its innate iron-withholding pathways. This symposium paper summarizes the background for the “iron hypothesis” as it relates to transfusion of red blood cells after prolonged refrigerated storage. It also includes a summary of the data from recent murine and human studies, and concludes with a discussion of several unresolved questions arising from these published studies.